Tradition as a Resource: A Personal Trajectory - Hill, Michael (Journal for the academic study of religion, 2007)
This introductory article reflects on a personal interest in the concept of tradition. Two contrasting sociological approaches to tradition are examined, the first being the structural-functionalist treatment of tradition as embedded and institutionalized, the second the more dynamic Weberian approach to tradition which links it with charismatic breakthroughs. Using the latter, it is possible to speak of a ‘revolution by tradition’ and to indicate different referents of tradition in the Church of England. A recent study of Hawksmoor’s London churches shows the attempted embodiment of primitive tradition in their architecture. In a very different context, Maori prophetic movements in nineteenth-century New Zealand reveal the potential for tradition to provide a charismatic springboard. A third example of the innovative potential of tradition is located in the ‘Asian values’ debate, where a constructed cluster of values surrounding neo-Confucianism can be associated with what is termed ‘reverse Orientalism’. Ideological discourse in Singapore provides an important test of the ‘Asia Values’ model. Finally, features of each article in this special issue are highlighted.